2023
DOI: 10.1111/gcb.16720
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use intensification systematically alters the size structure of aquatic communities in the Neotropics

Abstract: Land-use and land-cover transitions can affect biodiversity and ecosystem functioning in a myriad of ways, including how energy is transferred within food-webs. Size spectra (i.e. relationships between body size and biomass or abundance) provide a means to assess how food-webs respond to environmental stressors by depicting how energy is transferred from small to larger organisms. Here, we investigated changes in the size spectrum of aquatic macroinvertebrates along a broad land-use intensification gradient (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 98 publications
1
10
0
Order By: Relevance
“…Previous work has investigated the accuracy and inherent biases associated with different estimation methods (Edwards et al, 2017(Edwards et al, , 2020White et al, 2007). However, the extent to which these inaccuracies and biases compound across Binning methods are easy to use and interpret, which most likely accounts for their wide use in ecological studies (Collyer et al, 2023;Martínez et al, 2016;Perkins et al, 2018). However, aggregating individuals into logarithmic bins removes a large amount of information within the data by collapsing body size variation into a single value within each bin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has investigated the accuracy and inherent biases associated with different estimation methods (Edwards et al, 2017(Edwards et al, , 2020White et al, 2007). However, the extent to which these inaccuracies and biases compound across Binning methods are easy to use and interpret, which most likely accounts for their wide use in ecological studies (Collyer et al, 2023;Martínez et al, 2016;Perkins et al, 2018). However, aggregating individuals into logarithmic bins removes a large amount of information within the data by collapsing body size variation into a single value within each bin.…”
Section: Discussionmentioning
confidence: 99%
“…Binning methods are easy to use and interpret, which most likely accounts for their wide use in ecological studies (Collyer et al., 2023; Martínez et al., 2016; Perkins et al., 2018). However, aggregating individuals into logarithmic bins removes a large amount of information within the data by collapsing body size variation into a single value within each bin.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also report results consistent with the use of size distributions to assess the impact of disturbance. Recent work by Collyer et al [137] (figure 2b) assessed the relationship between macroinvertebrate size structure along a human land-use gradient (a surrogate for increasing perturbation and disturbance) in subtropical Brazilian streams. Consistent with expectations in box 2, they found that the size distribution is characterized by an approximate inverse power law with many small individuals and few large (figure 2b).…”
Section: (E) Empirical Supportmentioning
confidence: 99%
“…Theory predicts that for size spectra in undisturbed trophic networks the exponent should begin to approximate −1 as is observed here. Data and figure redrawn from Collyer et al [137]. (ii) Forest tree size distribution recovering from disturbance from approximately 100 000 forests plots in North America spanning disturbance gradients.…”
Section: (E) Empirical Supportmentioning
confidence: 99%
“…Among these understudied ecosystems, streams of Brazilian Atlantic Rainforest are highly threatened through human land-use intensification and the substitution of forests to pasture and monoculture plantations (Siqueira et al, 2015). Since these ecosystems provide a myriad of services to human society, from fresh water and recreation to nutrient cycling (Meyer, 1997;Palmer et al, 2014), describing their food webs in well preserved regions is crucial to define the baseline in face of human impacts (Collyer et al, 2023).…”
Section: Introductionmentioning
confidence: 99%